Anti-caking fertilizer granules and preparation method and application thereof
The fertilizer granules prepared through specific proportions and preparation methods have solved the problems of existing fertilizer granules failing in humid environments, poor waterproofing performance and insufficient heat resistance, and achieved the stability and excellent performance of fertilizer granules in various environments, significantly reducing storage and transportation costs.
Patent Information
- Application Number
- CN202411327619.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing anti-caking fertilizer granules fail in humid environments, have poor waterproof performance, insufficient heat resistance, and may have adverse effects on the soil structure, and have poor usage stability.
The fertilizer granules are prepared through specific proportions and preparation methods to enhance their anti-caking, waterproof, and mild soil structure improvement properties.
Fertilizer granules maintain stability in various environments, significantly reduce storage and transportation costs, and have excellent anti-caking, waterproof, and mild soil improvement performance, with wide application prospects.
Smart Images

Figure BDA0005055853180000171 
Figure BDA0005055853180000181
Abstract
Description
Technical Field
[0001] The present application relates to the field of soil fertilizers, and in particular to an anti-caking fertilizer granule and a preparation method and application thereof. Background Art
[0002] In the agricultural field, fertilizer is one of the key factors in increasing crop yields. However, traditional fertilizers are prone to caking during storage and transportation, which not only affects the efficiency of fertilization, but may also cause blockage of fertilization equipment, thus affecting the smooth progress of agricultural production activities. In order to overcome these problems, researchers have developed a variety of fertilizer granules, aiming to prevent caking by improving the physical properties of the granules.
[0003] Anti-caking fertilizer granules are a specially treated form of fertilizer that is designed to prevent the fertilizer granules from clumping during storage and transportation. This clumping is usually caused by humidity, pressure and temperature changes, which can make the fertilizer difficult to flow, affect the operation of fertilizer equipment, and may cause uneven fertilizer application.
[0004] The anti-caking fertilizer granules in the prior art still have some technical problems. For example, some anti-caking agents may lose their effect in a humid environment and have poor waterproof performance, causing the fertilizer particles to re-clump. In addition, some anti-caking agents may have an adverse effect on the soil structure or gradually lose their anti-caking function over time. In addition, they have good anti-caking properties at room temperature, but are prone to stickiness and re-caking under certain high temperature environments, and have poor heat resistance.
[0005] Therefore, in order to solve the above problems, the present application provides an anti-caking fertilizer granule and a preparation method thereof. The fertilizer granules prepared in the present application can have excellent anti-caking properties while maintaining good waterproof and moisture-proof, heat-resistant and soil structure improvement properties, thereby avoiding the use and storage stability of the fertilizer granules in various environments, greatly reducing the storage and transportation costs and procedures of the fertilizer granules, and having very excellent application prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides an anti-caking fertilizer granule, which comprises the following raw materials, by weight: 40 to 60 parts of urea, 1 to 3 parts of ammonium humate, 10 to 20 parts of inorganic metal salt, 20 to 30 parts of phosphate, 1 to 5 parts of binder, 5 to 10 parts of functional resin, 5 to 10 parts of complexing agent, 10 to 15 parts of functional agent, and 1 to 3 parts of flow aid.
[0007] As a preferred solution, the mass ratio of urea, inorganic metal salt and phosphate is (50-60): (15-20): (22-26).
[0008] As a preferred solution, the mass ratio of urea, inorganic metal salt and phosphate is (50-55): (16-18): (24-25).
[0009] As a preferred solution, the mass ratio of urea, functional resin, complexing agent and functional agent is (50-60): (6-10): (7-9): (12-15).
[0010] As a preferred solution, the mass ratio of urea, functional resin, complexing agent and functional agent is (50-55): (8-10): (7-8): (13-14).
[0011] As a preferred solution, the inorganic metal salt is at least one of sodium bicarbonate, magnesium sulfate, potassium sulfate, potassium nitrate, potassium chloride, zinc sulfate, copper sulfate and calcium nitrate.
[0012] As a preferred solution, the inorganic metal salt is a combination of potassium sulfate and copper sulfate.
[0013] As a preferred solution, the mass ratio of potassium sulfate to copper sulfate is (3-4): (0.8-1.4).
[0014] As a preferred solution, the mass ratio of potassium sulfate to copper sulfate is (3.2-3.4): (0.9-1.2).
[0015] As a preferred solution, the phosphate is at least one of superphosphate, double superphosphate, monoammonium phosphate, diammonium phosphate, diammonium phosphate and potassium dihydrogen phosphate.
[0016] As a preferred solution, the phosphate is a combination of monoammonium phosphate and potassium dihydrogen phosphate.
[0017] As a preferred solution, the mass ratio of monoammonium phosphate to potassium dihydrogen phosphate is (4-4.5):(1-1.2).
[0018] As a preferred solution, the binder is at least one of carrageenan, gum arabic, polyethylene glycol, polyvinyl alcohol, sodium polyacrylate and carboxymethyl cellulose.
[0019] As a preferred solution, the binder is a composition of polyvinyl alcohol and carboxymethyl cellulose.
[0020] As a preferred solution, the mass ratio of polyvinyl alcohol to carboxymethyl cellulose is (2-2.2):(3-3.4).
[0021] As a preferred solution, the preparation method of the functional resin comprises the following steps: S1: adding starch to deionized water, stirring and mixing evenly, then adding sodium hydroxide and sodium perborate, stirring and mixing, reacting for 2 to 2.5 hours, centrifugally filtering and washing the product to obtain a pretreated starch material; S2: adding 2-hydroxyethyl acrylate, isopropyl acrylate and benzophenone to a reaction container, irradiating with a wavelength of 350 to 420 nm under nitrogen for 2 to 2.5 hours, filtering the precipitate after the reaction is completed, and washing with ethanol for 2 to 3 times to obtain a prepolymer; S3: adding the obtained prepolymer and the pretreated starch material to deionized water, heating to 80 to 85° C., stirring and keeping warm at 40 to 50 rpm for 40 to 45 minutes, then adding an initiator, sodium hexametaphosphate and acrylamide, stirring and keeping warm at 80 to 100 rpm for 4 to 4.5 hours, filtering the product after the reaction is completed, washing with ethanol and deionized water for 3 to 4 times in sequence, and cutting and granulating to obtain the product.
[0022] As a preferred solution, the starch is amylose, and the amylose content is 70-75%.
[0023] As a preferred solution, the mass ratio of the starch, sodium hydroxide and sodium perborate is (6-8): (0.4-0.8): (0.6-1).
[0024] As a preferred solution, the mass ratio of the pretreated starch material, 2-hydroxyethyl acrylate, isopropyl acrylate, sodium hexametaphosphate and acrylamide is (4-5): (1-2): (0.5-0.8): (0.2-0.3): (10-12).
[0025] As a preferred solution, the initiator is potassium persulfate or ammonium persulfate.
[0026] In the present application, by adding the above-mentioned functional resin, the stability of the fertilizer granules during storage and transportation can be greatly improved, and the fertilizer granules have excellent waterproof and moisture-proof, heat-resistant and soil structure improvement effects. The added functional resin can be used as a matrix to entangle the molecular chains through the spiral molecular chain structure of branched starch in the preparation of the functional resin, accelerate the construction of the three-dimensional network in the functional resin, thereby greatly improving the density of the intermolecular structure of the functional resin itself. When added to the granules, the functional resin's more active groups can act as a good adhesive to enhance the strength of the interaction between the raw material molecules in the fertilizer granules, and can increase the overall cohesion of the particles through the entanglement effect so that the particles can still maintain a good particle shape under the action of external forces. In addition, due to the denser intermolecular structure, the penetration resistance of water molecules in the air to the granules can be greatly enhanced, thereby It can maintain good waterproof and moisture-proof effects during storage and transportation within the use period, and can also maintain good soil structure improvement and moisture retention effects during use; on the other hand, the addition of starch materials can also enhance the overall affinity of the functional resin in the soil, and can accelerate the degradation of the functional resin during long-term use, thereby improving its environmental friendliness. The prepared functional resin can increase the smooth resin content on the surface of the granules, provide a smooth granule surface, reduce the residence time of water molecules in the air on the surface of the granules during storage and transportation, and avoid the rough surface structure from helping the formation of the hydration layer, thereby obtaining good heat-resistant and moisture-proof effects.
[0027] As a preferred solution, the complexing aid is a polyglycine complex.
[0028] As a preferred scheme, the preparation method of the polyglycine complex comprises the following steps: S1: adding copper sulfate, zinc sulfate and polyglycine to a reaction container, adding deionized water, and adding citric acid to adjust the pH to 4.5-5.5; S2: heating to 50-55°C, then keeping the temperature for reaction for 2-3h, and during the reaction, the pH is always controlled to be 4.5-5.5 by adding citric acid to obtain a mixed liquid product; S3: after the reaction is completed, mixing the mixed liquid product with DTPA, keeping the temperature at 100-120rpm and 45-50°C and stirring for 2-2.5h, and then naturally cooling the mixture to room temperature for aging for 30-40min to obtain the product.
[0029] As a preferred solution, the mass ratio of copper sulfate, zinc sulfate and polyglycine is (1.2-1.5): (0.5-1): (3.2-3.5).
[0030] As a preferred solution, the added amount of DTPA is 5-10wt% of the mixed liquid product.
[0031] As a preferred solution, the functional auxiliary agent is a composition of epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth.
[0032] As a preferred solution, the mass ratio of the epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth is (3-4): (5-6): (2-2.5): (4-5).
[0033] As a preferred solution, the mass ratio of the epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth is (3.5-3.8): (5.2-5.4): (2.1-2.3): (4.4-4.6).
[0034] As a preferred solution, the epoxy block compound is ethylene oxide-propylene oxide block copolyether.
[0035] As a preferred solution, the epoxy block material is a composition of ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 4500-5000 and a weight average molecular weight of 8000-8500.
[0036] As a preferred solution, the mass ratio of the ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 4500-5000 and the weight average molecular weight of 8000-8500 is (4-5): (1.2-1.5).
[0037] As a preferred solution, the C13-15 fatty alcohol polyoxyethylene ether is an isomeric C13 fatty alcohol polyoxyethylene ether.
[0038] As a preferred solution, the hydroxyl value of the isomeric C13 fatty alcohol polyoxyethylene ether is 100-140 mgKOH / g.
[0039] As a preferred solution, the average particle size of the diatomaceous earth is 3 to 5 μm.
[0040] As a preferred solution, the average porosity of the diatomaceous earth is 80-90%.
[0041] The above-mentioned functional additives added in this application can effectively improve the waterproof and moisture-proof, temperature-resistant and soil structure improvement performance of fertilizer granules. First, the combined effect of the added epoxy block and diatomite can greatly increase the mutual adhesion of molecules in the granules, enhance the bonding effect between small particles, and in the formation process of the granules, can work together with the added functional resin to improve the smoothness of the granule surface, thereby greatly reducing the formation speed of the hydration layer on the surface of the granules, and improve the fluidity of the granule raw materials on the basis of improving the waterproof and moisture-proof effect, improve its particle formation completion, and have good anti-caking performance; secondly, the added C13-15 fatty alcohol polyoxyethylene ether and phenethylphenol polyoxyethylene ether can greatly reduce the surface tension between the raw material particles, and can enhance the loading effect of the raw material particles in diatomite, in addition to being able to greatly improve the dispersion uniformity of the raw material particles, it can also absorb the excess water inside the granules, reduce the aggregation of water molecules, and prevent the adhesion between particles, thereby effectively reducing caking, and improving the overall waterproof and temperature-resistant effects of the granules.
[0042] As a preferred solution, the glidant is a combination of microcrystalline cellulose and magnesium stearate.
[0043] As a preferred solution, the mass ratio of microcrystalline cellulose to magnesium stearate is (2-3): (0.6-1.2).
[0044] The second aspect of the present application provides a method for preparing the above-mentioned anti-caking fertilizer granules, which specifically includes the following steps: S1: urea, ammonium humate, inorganic metal salt and phosphate are mixed and sieved to remove impurities; S2: the raw materials in S1 are added to a mixer and stirred at 80-100rpm for 15-20min, then a binder, a functional resin, a complexing agent and a functional agent are added and continued to be mixed and dispersed for 10-15min, and finally a flow aid is added and stirred for 5-8min to obtain a mixture; S3: the mixture is added to a granulator, the temperature is controlled to 80-100°C for extrusion granulation, and after the granulation is completed, the particles are cooled to room temperature in a cooler under a dry environment, and the cooled particles are screened through a vibrating screen to remove unqualified particles.
[0045] The third aspect of the present application provides an application of the above-mentioned anti-caking fertilizer granules in field crop planting, cash crop planting, landscaping, greenhouse cultivation, pasture cultivation and compound fertilizer.
[0046] The beneficial effects of this application are:
[0047] 1. The anti-caking fertilizer granules provided in the present application have excellent anti-caking properties while maintaining good waterproof and moisture-proof, heat-resistant and soil structure improvement properties, avoiding the use and storage stability of the fertilizer granules in various environments, greatly reducing the storage and transportation costs and procedures of the fertilizer granules, and having very excellent application prospects.
[0048] 2. The anti-caking fertilizer granules provided in the present application can enhance the strength of the interaction between the raw material molecules in the fertilizer granules and increase the cohesion of the granules by adding functional resins through their good adhesive effect; and because the addition of functional resins can also form a relatively dense intermolecular structure, the penetration resistance of water molecules in the air to the granules can be greatly enhanced, thereby maintaining good waterproof and moisture-proof effects during storage and transportation within the use period, and can also maintain good soil structure improvement and moisture retention effects during use; on the other hand, the addition of starch materials can also enhance the overall affinity of the functional resin in the soil, and can accelerate the degradation of the functional resin in long-term use, thereby improving its environmental friendliness, and the prepared functional resin can increase the smooth resin content on the surface of the granules, provide a flat granule surface, reduce the residence time of water molecules in the air on the surface of the granules during storage and transportation, and avoid the help of the rough surface structure in the formation of the hydration layer, thereby obtaining good heat-resistant and moisture-proof effects.
[0049] 3. The anti-caking fertilizer granules provided in the present application have specific functional additives added thereto, which can effectively improve the waterproof and moisture-proof, heat-resistant and soil structure-improving properties of the fertilizer granules; the added epoxy block and diatomaceous earth can significantly increase the mutual adhesion of the molecules in the granules, enhance the bonding effect between small particles, and in the formation process of the granules, can work together with the added functional resin to improve the smoothness of the granule surface, thereby significantly reducing the formation rate of the hydration layer on the surface of the granules, and on the basis of improving the waterproof and moisture-proof effect, improve the fluidity of the granule raw materials, improve the completion of its particle formation, and have good anti-caking properties; secondly, the added C13-15 fatty alcohol polyoxyethylene ether and phenethylphenol polyoxyethylene ether can significantly reduce the surface tension between the raw material particles, and can enhance the loading effect of the raw material particles in the diatomaceous earth, in addition to significantly improving the dispersion uniformity of the raw material particles, it can also absorb excess water inside the granules, reduce the aggregation of water molecules, and prevent the adhesion between particles, thereby effectively reducing caking and improving the overall waterproof and heat-resistant effects of the granules. DETAILED DESCRIPTION
[0050] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0051] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0052] Example 1
[0053] Example 1 The first aspect provides an anti-caking fertilizer granule, in which the raw materials are, by mass: 52.5 parts of urea, 2.2 parts of ammonium humate, 17.4 parts of inorganic metal salt, 24.5 parts of phosphate, 3.2 parts of binder, 9.6 parts of functional resin, 7.2 parts of complexing agent, 13.4 parts of functional agent, and 2.1 parts of flow aid.
[0054] Urea was purchased from the 46% N-type urea product sold by Sinochem Group.
[0055] The inorganic metal salt is a combination of potassium sulfate and copper sulfate, and the mass ratio of the two is 3.3:1.1.
[0056] The phosphate is a composition of monoammonium phosphate and potassium dihydrogen phosphate, and the mass ratio of the two is 4.2:1.
[0057] The binder is a composition of polyvinyl alcohol 2000 and carboxymethyl cellulose, and the mass ratio of the two is 2.2:3.3.
[0058] The preparation method of the functional resin comprises the following steps, calculated by mass: S1: adding 7.2 parts of amylose to 200 parts of deionized water, stirring and mixing, adding 0.68 parts of sodium hydroxide and 0.72 parts of sodium perborate, stirring and mixing, reacting for 2.2 hours, centrifuging and filtering the product, washing, and obtaining a pretreated starch material; S2: adding 1.6 parts of 2-hydroxyethyl acrylate, 0.7 parts of isopropyl acrylate, and 0.1 parts of benzophenone to a reaction container, irradiating the reaction vessel under nitrogen at a wavelength of 380 nm for 2 hours. h, after the reaction is completed, the precipitate is filtered and washed with ethanol for 3 times to obtain a prepolymer; S3: the obtained prepolymer and 4.4 parts of pretreated starch are added into 220 parts of deionized water and heated to 85°C, stirred at 45rpm and kept warm for 45min, then 0.12 parts of potassium persulfate, 0.28 parts of sodium hexametaphosphate and 11.8 parts of acrylamide are added, and the mixture is stirred at 100rpm and kept warm for 4.5h. After the reaction is completed, the product is filtered, washed with ethanol and deionized water for 4 times in sequence, and cut and granulated.
[0059] The linear content of amylose was 72.4%, and the corresponding amylose product was purchased from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.
[0060] The complexing aid is a polyglycine complex, and the preparation method of the polyglycine complex comprises the following steps, calculated by mass: S1: 1.4 parts of copper sulfate, 0.8 parts of zinc sulfate and 3.3 parts of polyglycine are mixed and added into a reaction container, 150 parts of deionized water are added, and citric acid is added to adjust the pH to 5.2; S2: the temperature is raised to 55°C, and then the temperature is kept for reaction for 3 hours, and during the reaction, the pH is always controlled within the range of 5.1 to 5.3 by adding citric acid to obtain a mixed liquid product; S3: after the reaction is completed, the mixed liquid product is mixed with DTPA (the amount added is 7.5wt% of the mixed liquid product), and the mixture is kept stirred at a speed of 100rpm and 50°C for 2.5 hours, and then the mixture is naturally cooled to room temperature 25°C and aged for 40 minutes to obtain the product.
[0061] Polyglycine was purchased from the polyglycine products sold by Xi'an Ruixi Biotechnology Co., Ltd.
[0062] The functional additive is a composition of epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth, and the mass ratio of the four is 3.6:5.3:2.2:4.4.
[0063] Phenethylphenol polyoxyethylene ether was purchased from the Nongru 601 model product of Xingtai Xinlanxing Technology Co., Ltd.
[0064] The epoxy block is a composition of ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 4600 (purchased from BASF L85 model product) and a weight average molecular weight of 8400 (purchased from BASF L68 model product), and the mass ratio of the two is 4.6:1.4.
[0065] C13-15 fatty alcohol polyoxyethylene ether is isomeric C13 fatty alcohol polyoxyethylene ether with a hydroxyl value of 120 mgKOH / g, and is purchased from Hai'an Guoyun Chemical Co., Ltd. under the model E-1306.
[0066] The diatomaceous earth had an average particle size of 4.2 μm and an average porosity of 84.4%. The diatomaceous earth was purchased from Imerys Minerals Company and was a product of model Diatomaceous Earth (DE) 956.
[0067] The glidant is a composition of microcrystalline cellulose and magnesium stearate, and the mass ratio of the two is 2.6:0.8.
[0068] Microcrystalline cellulose was purchased from Xi'an Musen Bioengineering Co., Ltd., a food-grade microcrystalline cellulose product.
[0069] The second aspect of the present embodiment provides a method for preparing the above-mentioned anti-caking fertilizer granules, which specifically includes the following steps: S1: urea, ammonium humate, inorganic metal salt and phosphate are mixed and sieved to remove impurities; S2: the raw materials in S1 are added to a mixer and stirred at 100rpm for 15 minutes, then a binder, a functional resin, a complexing agent and a functional agent are added and continued to be mixed and dispersed for 12 minutes, and finally a flow aid is added and stirred for 6 minutes to obtain a mixture; S3: the mixture is added to a granulator, the temperature is controlled to 95°C for extrusion granulation, and after granulation is completed, the particles are cooled to room temperature in a cooler under a dry environment, and the cooled particles are screened through a vibrating screen to remove unqualified particles.
[0070] Example 2
[0071] Example 2 The first aspect provides an anti-caking fertilizer granule, the raw materials of which are, by mass, 60 parts of urea, 2.2 parts of ammonium humate, 15.2 parts of inorganic metal salt, 25.8 parts of phosphate, 3.2 parts of binder, 7.5 parts of functional resin, 8.8 parts of complexing agent, 12.2 parts of functional agent, and 2.3 parts of flow aid.
[0072] Urea was purchased from the 46% N-type urea product sold by Sinochem Group.
[0073] The inorganic metal salt is a combination of potassium sulfate and copper sulfate, and the mass ratio of the two is 3.3:1.1.
[0074] The phosphate is a composition of monoammonium phosphate and potassium dihydrogen phosphate, and the mass ratio of the two is 4.2:1.
[0075] The binder is a composition of polyvinyl alcohol 2000 and carboxymethyl cellulose, and the mass ratio of the two is 2.2:3.3.
[0076] The preparation method of the functional resin comprises the following steps, calculated by mass: S1: adding 7.2 parts of amylose to 200 parts of deionized water, stirring and mixing, adding 0.68 parts of sodium hydroxide and 0.72 parts of sodium perborate, stirring and mixing, reacting for 2.2 hours, centrifuging and filtering the product, washing, and obtaining a pretreated starch material; S2: adding 1.6 parts of 2-hydroxyethyl acrylate, 0.7 parts of isopropyl acrylate, and 0.1 parts of benzophenone to a reaction container, irradiating the reaction vessel under nitrogen at a wavelength of 380 nm for 2 hours. h, after the reaction is completed, the precipitate is filtered and washed with ethanol for 3 times to obtain a prepolymer; S3: the obtained prepolymer and 4.4 parts of pretreated starch are added into 220 parts of deionized water and heated to 85°C, stirred at 45rpm and kept warm for 45min, then 0.12 parts of potassium persulfate, 0.28 parts of sodium hexametaphosphate and 11.8 parts of acrylamide are added, and the mixture is stirred at 100rpm and kept warm for 4.5h. After the reaction is completed, the product is filtered, washed with ethanol and deionized water for 4 times in sequence, and cut and granulated.
[0077] The linear content of amylose was 72.4%, and the corresponding amylose product was purchased from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.
[0078] The complexing aid is a polyglycine complex, and the preparation method of the polyglycine complex comprises the following steps, calculated by mass: S1: 1.4 parts of copper sulfate, 0.8 parts of zinc sulfate and 3.3 parts of polyglycine are mixed and added into a reaction container, 150 parts of deionized water are added, and citric acid is added to adjust the pH to 5.2; S2: the temperature is raised to 55°C, and then the temperature is kept for reaction for 3 hours, and during the reaction, the pH is always controlled within the range of 5.1 to 5.3 by adding citric acid to obtain a mixed liquid product; S3: after the reaction is completed, the mixed liquid product is mixed with DTPA (the amount added is 7.5wt% of the mixed liquid product), and the mixture is kept stirred at a speed of 100rpm and 50°C for 2.5 hours, and then the mixture is naturally cooled to room temperature 25°C and aged for 40 minutes to obtain the product.
[0079] The functional additive is a composition of epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth, and the mass ratio of the four is 3.6:5.3:2.2:4.4.
[0080] The epoxy block is a composition of ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 4600 (purchased from BASF L85 model product) and a weight average molecular weight of 8400 (purchased from BASF L68 model product), and the mass ratio of the two is 4.6:1.4.
[0081] C13-15 fatty alcohol polyoxyethylene ether is isomeric C13 fatty alcohol polyoxyethylene ether with a hydroxyl value of 120 mgKOH / g, and is purchased from Hai'an Guoyun Chemical Co., Ltd. under the model E-1306.
[0082] The diatomaceous earth had an average particle size of 4.2 μm and an average porosity of 84.4%. The diatomaceous earth was purchased from Imerys Minerals Company and was a product of model Diatomaceous Earth (DE) 956.
[0083] The glidant is a composition of microcrystalline cellulose and magnesium stearate, and the mass ratio of the two is 2.6:0.8.
[0084] The second aspect of the present embodiment provides a method for preparing the above-mentioned anti-caking fertilizer granules, which specifically includes the following steps: S1: urea, ammonium humate, inorganic metal salt and phosphate are mixed and sieved to remove impurities; S2: the raw materials in S1 are added to a mixer and stirred at 100rpm for 15 minutes, then a binder, a functional resin, a complexing agent and a functional agent are added and continued to be mixed and dispersed for 12 minutes, and finally a flow aid is added and stirred for 6 minutes to obtain a mixture; S3: the mixture is added to a granulator, the temperature is controlled to 95°C for extrusion granulation, and after granulation is completed, the particles are cooled to room temperature in a cooler under a dry environment, and the cooled particles are screened through a vibrating screen to remove unqualified particles.
[0085] Comparative Example 1
[0086] The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the anti-caking fertilizer granules, in parts by mass, the raw materials are: 65.5 parts of urea, 2.2 parts of ammonium humate, 17.4 parts of inorganic metal salt, 24.5 parts of phosphate, 3.2 parts of binder, 2.5 parts of functional resin, 7.2 parts of complexing aid, 19.5 parts of functional aid, and 2.1 parts of flow aid.
[0087] Comparative Example 2
[0088] The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the anti-caking fertilizer granules, in parts by mass, the raw materials are: 52.5 parts of urea, 2.2 parts of ammonium humate, 17.4 parts of inorganic metal salt, 24.5 parts of phosphate, 3.2 parts of binder, 18.5 parts of functional resin, 7.2 parts of complexing aid, 5.5 parts of functional aid, and 2.1 parts of flow aid.
[0089] Comparative Example 3
[0090] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional resin comprises the following steps, calculated by mass: S1: adding 15.5 parts of amylose to 200 parts of deionized water, stirring and mixing, adding 0.3 parts of sodium hydroxide and 0.25 parts of sodium perborate, stirring and mixing for 2 hours, centrifuging and filtering the product, washing and obtaining a pretreated starch material; S2: adding 1.6 parts of 2-hydroxyethyl acrylate, 0.7 parts of isopropyl acrylate and 0.1 parts of benzophenone to The reaction vessel was irradiated with a wavelength of 380 nm under nitrogen for 2 hours. After the reaction, the precipitate was filtered and washed with ethanol for 3 times; S3: 4.4 parts of pretreated starch material were added to 220 parts of deionized water and heated to 85°C, stirred at 45 rpm for 45 minutes, then 0.12 parts of potassium persulfate, 0.28 parts of sodium hexametaphosphate and 11.8 parts of acrylamide were added, and the reaction was stirred at 100 rpm for 4.5 hours. After the reaction was completed, the product was filtered, washed with ethanol and deionized water for 4 times in turn, and cut into granules.
[0091] Comparative Example 4
[0092] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional resin comprises the following steps, by mass: S1: adding 7.2 parts of amylose to 200 parts of deionized water, stirring and mixing, adding 0.68 parts of sodium hydroxide and 0.72 parts of sodium perborate, stirring and mixing for 2.2 hours, centrifuging and filtering the product, washing and obtaining a pretreated starch material; S2: adding 2.4 parts of 2-hydroxyethyl acrylate, 1.5 parts of isopropyl acrylate and 0.18 parts of benzophenone The mixture was placed in a reaction vessel and irradiated with a wavelength of 380 nm under nitrogen for 2 hours. After the reaction, the precipitate was filtered and washed with ethanol for 3 times. S3: 2 parts of pretreated starch material were added to 220 parts of deionized water and heated to 85°C, stirred at 45 rpm for 45 minutes, then 0.14 parts of potassium persulfate, 0.44 parts of sodium hexametaphosphate and 15.5 parts of acrylamide were added, and the mixture was stirred at 100 rpm for 4.5 hours. After the reaction, the product was filtered, washed with ethanol and deionized water for 4 times, and cut into granules.
[0093] Comparative Example 5
[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional additive is a composition of epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth, and the mass ratio of the four is 1.2:8:1:6.
[0095] Comparative Example 6
[0096] The specific implementation method of this comparative example is basically the same as that of Example 1, except that the epoxy block is a composition of ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 1600 (purchased from BASF L42 model product) and a weight average molecular weight of 11000 (purchased from BASF L88 model product), and the mass ratio of the two is 4.6:1.4.
[0097] Comparative Example 7
[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of the diatomite is 13.5 μm, the average porosity is 72.6%, and the corresponding industrial-grade diatomite product is purchased from Chengdu Ding Hengda Chemical Products Co., Ltd.
[0099] Performance Evaluation
[0100] 1. Soil improvement: A corn planting plot in Shouguang City, Shandong Province was divided into 7 areas of 2 mu. During the test, the corn in the 7 plots was plowed 5 cm around each other, and the fertilizer granules prepared in the above embodiments and comparative examples were spread respectively, and then the soil was plowed again. The spreading amount was 12 kg / mu. The water retention rate of the soil on the day of fertilization was tested. After 7 days of normal maintenance, the water retention rate of the soil was tested again, and the percentage increase of the water retention rate of the soil before and after was calculated. The measured values were taken as the average of 10 tests and recorded in Table 1.
[0101] 2. Thermal stability: 250 g of the fertilizer granules prepared in the embodiments and comparative examples were sampled and stored in a constant temperature and humidity chamber at 65±3°C and 50±2% humidity for 30 days. The overall mass decomposition rate (mass reduction percentage %) of the fertilizer after 30 days of storage was calculated, and the average value of 10 measured values was recorded in Table 1; and at the same time, whether the fertilizer granules had obvious caking phenomenon, if so, it was recorded as unqualified, otherwise it was qualified, and 50 groups of samples were tested in each group, and the qualified rate of the samples in the 50 groups of samples was recorded, and the results were recorded in Table 1.
[0102] 3. Waterproof and moisture proof: 250 g of the fertilizer granules prepared in the examples and comparative examples were sampled and stored in a constant temperature and humidity chamber at 35±3°C and 90±2% humidity for 30 days. The samples were taken out after 30 days to observe whether the fertilizer granules had obvious agglomeration. If so, they were marked as unqualified, otherwise, they were qualified. 50 groups of samples were tested in each group, and the qualified rate of the samples in the 50 groups was recorded. The results are recorded in Table 1.
[0103] Table 1 Performance test results
[0104]
[0105]
[0106] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of soil improvement, waterproof and moisture-proof performance, and temperature resistance. This is mainly due to the combined effect of the functional resin, functional additives and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. An anti-caking fertilizer granule, characterized in that: The raw materials are as follows: 40-60 parts of urea, 1-3 parts of ammonium humate, 10-20 parts of inorganic metal salt, 20-30 parts of phosphate, 1-5 parts of binder, 5-10 parts of functional resin, 5-10 parts of complexing agent, 10-15 parts of functional agent, and 1-3 parts of flow aid. The inorganic metal salt is at least one of sodium bicarbonate, magnesium sulfate, potassium sulfate, potassium nitrate, potassium chloride, zinc sulfate, copper sulfate and calcium nitrate; The phosphate is at least one of superphosphate, triple superphosphate, monoammonium phosphate, diammonium phosphate, diammonium phosphate and potassium dihydrogen phosphate; The binder is at least one of carrageenan, gum arabic, polyethylene glycol, polyvinyl alcohol, sodium polyacrylate and carboxymethyl cellulose; The preparation method of the functional resin comprises the following steps: S1: adding starch to deionized water, stirring and mixing evenly, then adding sodium hydroxide and sodium perborate, stirring and mixing for reaction for 2-2.5 hours, centrifugally filtering and washing the product to obtain a pretreated starch material; S2: adding 2-hydroxyethyl acrylate, isopropyl acrylate and benzophenone to a reaction container, irradiating for reaction for 2-2.5 hours under nitrogen at a wavelength of 350-420 nm, filtering the precipitate after the reaction is completed, and washing with ethanol for 2-3 times to obtain a prepolymer; S3: adding the obtained prepolymer and the pretreated starch material to deionized water, heating to 80-85° C., stirring and keeping warm at 40-50 rpm for 40-45 minutes, then adding an initiator, sodium hexametaphosphate and acrylamide, stirring and keeping warm at 80-100 rpm for reaction for 4-4.5 hours, filtering the product after the reaction is completed, washing with ethanol and deionized water for 3-4 times in sequence, and cutting and granulating to obtain the product; The starch is amylose, and the amylose content is 70-75%; The mass ratio of the starch, sodium hydroxide and sodium perborate is (6-8): (0.4-0.8): (0.6-1); The mass ratio of the pretreated starch material, 2-hydroxyethyl acrylate, isopropyl acrylate, sodium hexametaphosphate and acrylamide is (4-5): (1-2): (0.5-0.8): (0.2-0.3): (10-12); The functional additive is a composition of epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth; The mass ratio of the epoxy block, C13-15 fatty alcohol polyoxyethylene ether, phenethylphenol polyoxyethylene ether and diatomaceous earth is (3-4): (5-6): (2-2.5): (4-5); The epoxy block material is an ethylene oxide-propylene oxide block copolyether; the epoxy block material is a composition of an ethylene oxide-propylene oxide block copolyether having a weight average molecular weight of 4500-5000 and a weight average molecular weight of 8000-8500; The mass ratio of the ethylene oxide-propylene oxide block copolyether with a weight average molecular weight of 4500-5000 and the weight average molecular weight of 8000-8500 is (4-5): (1.2-1.5); The C13~15 fatty alcohol polyoxyethylene ether is an isomeric C13 fatty alcohol polyoxyethylene ether; The average particle size of the diatomite is 3-5 μm; the average porosity of the diatomite is 80-90%; The complexing aid is a polyglycine complex; the preparation method of the polyglycine complex comprises the following steps: S1: adding copper sulfate, zinc sulfate and polyglycine to a reaction container, adding deionized water, and adding citric acid to adjust the pH to 4.5-5.5; S2: heating to 50-55°C, then keeping the temperature for reaction for 2-3 hours, and during the reaction, the pH is always controlled to be 4.5-5.5 by adding citric acid to obtain a mixed liquid product; S3: after the reaction is completed, mixing the mixed liquid product with DTPA, keeping the temperature at 100-120 rpm and 45-50°C for 2-2.5 hours, and then naturally cooling the mixture to room temperature for aging for 30-40 minutes to obtain the product; The mass ratio of copper sulfate, zinc sulfate and polyglycine is (1.2-1.5): (0.5-1): (3.2-3.5); the amount of DTPA added is 5-10wt% of the mixed liquid product; The glidant is a composition of microcrystalline cellulose and magnesium stearate; the mass ratio of the microcrystalline cellulose to magnesium stearate is (2-3): (0.6-1.2).
2. The anti-caking fertilizer granules according to claim 1, characterized in that: The mass ratio of the urea, the inorganic metal salt and the phosphate is (50-60): (15-20): (22-26).
3. The anti-caking fertilizer granules according to claim 2, characterized in that: The mass ratio of the urea, the functional resin, the complexing agent and the functional agent is (50-60): (6-10): (7-9): (12-15).
4. The anti-caking fertilizer granules according to claim 3, characterized in that: The inorganic metal salt is a combination of potassium sulfate and copper sulfate; the mass ratio of potassium sulfate to copper sulfate is (3-4): (0.8-1.4).
5. The anti-caking fertilizer granules according to claim 4, characterized in that: The phosphate is a composition of monoammonium phosphate and potassium dihydrogen phosphate; the mass ratio of the monoammonium phosphate to potassium dihydrogen phosphate is (4-4.5):(1-1.2).
6. The anti-caking fertilizer granules according to claim 5, characterized in that: The binder is a composition of polyvinyl alcohol and carboxymethyl cellulose; the mass ratio of the polyvinyl alcohol to the carboxymethyl cellulose is (2-2.2): (3-3.4).
7. The anti-caking fertilizer granules according to claim 6, characterized in that: The mass ratio of the copper sulfate, zinc sulfate and polyglycine is (1.2-1.5): (0.5-1): (3.2-3.5); the amount of DTPA added is 5-10wt% of the mixed liquid product.
8. A method for preparing the anti-caking fertilizer granules according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: urea, ammonium humate, inorganic metal salt and phosphate are mixed and sieved to remove impurities; S2: the raw materials in S1 are added to a mixer and stirred at 80-100 rpm for 15-20 minutes, then a binder, functional resin, complexing agent and functional agent are added and continued to be mixed and dispersed for 10-15 minutes, and finally a flow aid is added and stirred for 5-8 minutes to obtain a mixture; S3: the mixture is added to a granulator, the temperature is controlled at 80-100°C for extrusion granulation, and after granulation, the particles are cooled to room temperature in a cooler under a dry environment, and the cooled particles are screened through a vibrating screen to remove unqualified particles.
9. Use of the anti-caking fertilizer granules according to any one of claims 1 to 7 in field crop planting, cash crop planting, gardening, greenhouse cultivation, pasture cultivation and compound fertilizer.
Citation Information
Patent Citations
Temperature sensitive type slow-release pesticide for preventing and treating oriental fruit moth by using insect repellent plant and preparation method thereof
CN106719781A
Lignin-based thermosetting resin coated controlled-release fertilizer and production method thereof
CN107141094A